2011
DOI: 10.1088/0004-637x/741/2/89
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Distribution of Oh and Cn Radicals in the Coma of Comet Encke

Abstract: Multiple potential parent species have been proposed to explain CN abundances in comet comae, but the parent has not been definitively identified for all comets. This study examines the spatial distribution of CN radicals in the coma of comet Encke and determines the likelihood that CN is a photodissociative daughter of HCN in the coma. Comet Encke is the shortest orbital period (3.3 years) comet known and also has a low dust-to-gas ratio based on optical observations. Observations of CN were obtained from 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…These results were confirmed by Festou and Barale (2000). However, later (2003 apparition) Woodney et al (2007) and Ihalawela et al (2011) did not confirm the presence of two active areas on the surface of the comet's nucleus and instead suggested the possibility of a single active area which forms single-cone jet with an opening angle of 90 � .…”
Section: Discussionmentioning
confidence: 96%
“…These results were confirmed by Festou and Barale (2000). However, later (2003 apparition) Woodney et al (2007) and Ihalawela et al (2011) did not confirm the presence of two active areas on the surface of the comet's nucleus and instead suggested the possibility of a single active area which forms single-cone jet with an opening angle of 90 � .…”
Section: Discussionmentioning
confidence: 96%
“…A simple model like the Haser model cannot do these data justice. A more complicated model, such as proposed by Ihalawela et al (2011), allows for deviations from spherical symmetry. However, it should be noted that if we independently fit the different position angles in these Encke data with the Haser model (using both sides of the optocenter together in a single fit), we get the same CN production rate for each position angle (even though the fits look bad).…”
Section: Reduction and Analysismentioning
confidence: 99%
“…CH3CN is also difficult to measure and was only seen in Hartley 2 in minor quantities from the EPOXI flyby (Boice 2013), but this potential parent was detected in comets Hale-Bopp, Hyakutake, IkeyaZhang, and Lemmon Bockelée-Morvan et al, 2004;and Remijan et al, 2008) Crovisier et al (1994), which tabulated five other independent measurements of the HCN lifetime that closely agree to each another. Coma studies of short-period comet Encke showed a similar inconsistency when using HCN as the sole CN parent with the vectorial model (Ihalawela et al, 2011). Boissier et al (2013) hypothesized that the HCN scale length issue may be due to HCN emanating from extended icy grains, but having grains as a source of HCN would then exacerbate the Haser fits since the overall scale length would unavoidably increase (i.e., the scale length needs to be lower for HCN to have a better fit for the data presented here).…”
Section: Discussion Of Haser Resultsmentioning
confidence: 98%